Exposure to household air pollution from biomass‐burning cookstoves and HbA1c and diabetic status among Honduran women. (27th June 2018) - Rajkumar, S.; Clark, M. L.; Young, B. N.; Benka‐Coker, M. L.; Bachand, A. M.; Brook, R. D.; Nelson, T. L.; Volckens, J.; Reynolds, S. J.; L'Orange, C.; Good, N.; Koehler, K.; et al.
Abstract: Household air pollution from biomass cookstoves is estimated to be responsible for more than two and a half million premature deaths annually, primarily in low and middle‐income countries where cardiometabolic disorders, such as Type II Diabetes, are increasing. Growing evidence supports a link between ambient air pollution and diabetes, but evidence for household air pollution is limited. This cross‐sectional study of 142 women (72 with traditional stoves and 70 with cleaner‐burning Justa stoves) in rural Honduras evaluated the association of exposure to household air pollution (stove type, 24‐hour average kitchen and personal fine particulate matter [PM2.5 ] mass and black carbon) with glycated hemoglobin (HbA1c) levels and diabetic status based on HbA1c levels. The prevalence ratio (PR) per interquartile range increase in pollution concentration indicated higher prevalence of prediabetes/diabetes (vs normal HbA1c) for all pollutant measures (eg, PR per 84 μg/m 3 increase in personal PM2.5, 1.49; 95% confidence interval [CI], 1.11‐2.01). Results for HbA1c as a continuous variable were generally in the hypothesized direction. These results provide some evidence linking household air pollution with the prevalence of prediabetes/diabetes, and, if confirmed, suggest that the global public health impact of household air pollution may be broader than currently estimated.